Lifetime assessment of porous journal bearings using joint time-frequency analysis of real-time sensor data. (May 2022) - Prost, J.; Boidi, G.; Varga, M.; Vorlaufer, G.; Eder, S.J.
Abstract: In this work, we employed a custom-built tribometer that allows simultaneous testing of five porous journal bearing systems to perform lifetime tests on combinations of bearing materials and lubricants at various temperatures. Test parameters and contact conditions were tailored to promote mixed/boundary lubrication and accelerated wear tests. Failure and wear data were evaluated ex-post, leading to survival probability curves based on Weibull fitting that allow quantitative ranking of bearing life as well as qualitative assessment of the failure behavior. Friction torque and accelerometer data were recorded either continuously or at regular time intervals, with the potential for on-the-fly evaluation. Using joint time-frequency analysis, we produced spectograms of the accelerometer data, which can characterize the state of operation and allow a clear disambiguation of the running-in phase, steady-state behavior, and critical operation before failure. Graphical Abstract: ga1 Highlights: Custom-built, heatable porous journal bearing tribometer with 5 parallel benches. Joint time-frequency analysis of accelerometer data for operation regime detection. High-throughput lifetime assessment of bearing systems via Weibull statistics. Possible applications in material/lubricant development and predictive maintenance.